Public perception of the performance of the Medan City government: The role of public services, community participation, accountability, and transparency from a Sharia perspective - Sari, Novi Purnama; Ramadhani, Sri; Soemitra, Andri (LPMP Imperium, 2025)
This study examines the influence of public services, community participation, transparency, and accountability on public perceptions of the performance of the Medan City Government from a Sharia perspective. Using purposive sampling, several respondents were selected to participate in a survey. The results of the analysis show that public services and transparency have a positive and significant influence on public perceptions. Meanwhile, community participation and accountability do not show a significant impact. This research model explains most of the variation in public perception. The Sharia approach reinforces ethical and fairness aspects in government administration. This study recommends improving the quality of public services and transparency as key factors in enhancing public perception and building the City of Medan's government legitimacy sustainably. Public interest statements This research is important to improve governance in Medan City through enhanced public services and transparency, by Sharia principles, in order to increase public trust and welfare fairly and sustainably.